Environmental Management Accounting (EMA) practices and plastic pollution control in selected food and beverage firms - Smangele Nzama; Odunayo Magret Olarewaju; Omolola A Arise; Idris Ganiyu (Cogent Business & Management, 2022)
This study investigated the relationship between EMA and plastic pollution control. The study concentrated on Food and Beverage manufacturing companies since they use plastic goods to package their products. Plastic products are discarded once they have served their purpose, which pollutes the environment. A quantitative approach was adopted, with 124 self-completed questionnaires being administered to financial managers, management accountants, factory accountants and chief accountants of 38 selected food and beverage manufacturing firms in Durban. The findings revealed a significant relationship between environmental information and environmentally-related activities. Environmental information also had a positive relationship with corporate environmental strategy. Moreover, a strong positive relationship was discovered between environmental information and plastic pollution control. An analysis of the link between environmentally-related activities and plastic pollution control revealed an insignificant relationship. An insignificant relationship was also discovered between corporate environmental strategy and plastic pollution control. This study suggests that companies within the Food and Beverage industry must put in place sustainable environmental strategies, whereby eco-friendly disposal initiatives must be implemented for plastic waste management.
Keywords: 650; accounting information; corporate strategy; CSR; environmental management; Environmental sustainability; plastic waste